Electro-activated peroxymonosulfate and peroxydisulfate oxidation of leachate nanofiltration concentrate: multiple-response optimization - Varank, G.; Yazici Guvenc, S.; Demir, A. (SPRINGER, 2020)
In this study, the performance of electro-peroxymonosulfate and electro-peroxydisulfate methods in biologically stabilized leachate nanofiltration concentrate treatment was investigated. To increase treatability and biodegradability of the concentrated leachate was aimed. Central composite design was applied for the optimization of process parameters and development of mathematical model. Variance analyses were performed to attain the interaction among the responses and process variables and to analyze the data. Second-order regression models were developed by Statgraphics Centurion XVI.I software program in order to estimate the removal efficiencies. Model's correlation coefficients for COD removal through electro-peroxymonosulfate and electro-peroxydisulfate processes were determined to be 0.8769 and 0.8910, respectively, expressing conformity of the experimental data to the model. COD removal rates obtained through electro-peroxymonosulfate and electro-peroxydisulfate processes under optimum conditions (HSO5-/COD ratio: 2.5, current: 1.8 A, pH: 6.4 and reaction time: 35.9 min for electro-peroxymonosulfate process and S(2)O8-2/COD ratio: 1.9, current: 2.1 A, pH: 5.1 and reaction time: 32.3 min for electro-peroxydisulfate process) were determined as 84.2% and 79.6%, respectively. Before advanced treatment processes, the biodegradable COD fraction of leachate nanofiltration concentrate was 12.7% and the soluble COD fraction was 78.3%. After electro-peroxymonosulfate process, biodegradable COD fraction increased to the value of 44.6% and the soluble COD fraction increased to the value of 90.5%, whereas after electro-peroxydisulfate process, biodegradable COD fraction increased to the value of 37.5% and the soluble COD fraction increased to the value of 87.4%. The results of the study showed that electro-peroxymonosulfate and electro-peroxydisulfate oxidation processes were effective treatment methods for leachate concentrates with low biodegradability.
Keywords: Activated-sulfate radicals; Advanced oxidation; Central composite design; Concentrated leachate; COD fractions; MATURE LANDFILL LEACHATE; PHENOLIC WASTE-WATER; SURFACE METHODOLOGY; FENTON OXIDATION; ELECTROCOAGULATION PROCESS; REFRACTORY ORGANICS; AQUEOUS-SOLUTION; COAGULATION; DEGRADATION; REMOVAL; Environmental Sciences & Ecology